Six events that shaped antibody approvals in oncology - Paul, Suman; Zhou, Shibin (Frontiers in Immunology, 2025)
A little over twenty-five years ago, the European Medicines Agency (EMA) and the Food and Drug Administration (FDA) approved the chimeric antibody rituximab which fundamentally altered the landscape of anti-cancer drugs. While only a few antibodies were approved in the immediate years that followed the rituximab approval, the last decade saw a wave of antibody-drug approvals in the oncology arena. In the last three years, the EMA and FDA greenlighted eighteen antibodies, the majority of them designed in the formats of antibody-drug conjugates (ADC) and bispecific antibodies (BsAb). While the use of ADC and BsAb formats and the current rapid pace of approvals appear routine and almost inevitable, such progress was thought to be quite improbable in the early days of therapeutic antibody development. To understand how we arrived at the current state of antibody development in oncology, we focus on six monumental events that shaped antibody approvals over the last two and half decades. We examine the circumstances that led to the approval of rituximab and trastuzumab, the first successful antibodies for the treatment of hematologic and solid cancers. We detail the generation of the ADC and BsAb formats that dramatically augmented antibody-mediated precision cytotoxicity. Finally, we explore the development of ipilimumab, the first immune checkpoint-inhibiting antibody that activates the immune system to kill cancer cells, and the discovery that allowed the use of checkpoint inhibitors across all cancer types based on the presence of genetic markers. Revisiting these key events provides critical insights into the process of antibody development in oncology.